DETERMINAN STATUS PENYALAHGUNAAN NARKOBA PADA REMAJA USIA 15-24 TAHUN DI INDONESIA TAHUN 2017 - Sahara Sabilah Putri; Budyanra Budyanra (Seminar Nasional Official Statistics, 2020)
Illicit drug has become a global problem that obtain serious concern (BNN,2019). In Indonesia, drug abuser keeps increasing and among them are students both in school and college. In 2017, 24 out of 100 drug abusers in Indonesia are students. Based on 2018 BNN data, the percentage of students who abuse drugs in 13 provincial capitals of Indonesia is 3.2 percent or equivalent to 2.29 million adolescents. UNODC (2018) declared that adolescents are the most vulnerable group to falling into drug abuse problem. That occurs since adolescents are in their period of searching for identity and have a very high curiosity. In the process of finding their identity, adolescents often involved into negative things including drug abuse. This study was conducted to determine the factors that affect the status of drug abuse among adolescents 15-24 years in Indonesia using the 2017 IDHS data. The analytical method used is binary logistic regression. The results showed that the variables of gender, age, level of education, residence, smoking status, and alcohol consumption status had a significant influence on the status of drug abuse among adolescents in Indonesia.